Development of Visual Interactive Learning Media Model Based on Documentary Film Themes of Regional Tourism Potential in Tourism Geography Learning - Selamat Riadi; Nasruddin Nasruddin; Hanifah Mahat; Rendya Adi Kurniawan; Rizky Nur Hakimah (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
The tourism geography course is an elective course presented in semester 5 for students of the Geography Study Program at the Lambung Mangkurat University Banjarmasin, this course presents content-based contextual material. The content of the material about the natural potential and cultural potential of an area in the tourism geography course will be more concrete and easier to understand if the material is delivered with the help of documentary films with the theme of regional tourism potential. The aims of this research are to (1) design documentary film media to be used as a support for learning tourism geography courses for regional tourism potential; (2) know the feasibility of documentary film media to be used as a support for learning tourism geography courses for regional tourism potential; and (3) know student learning outcomes and student responses to documentary film media used as a support for learning tourism geography courses for regional tourism potential. The technique collection of the data is divided into two stages: (1) Pre Production, and (2) Production. An increase in the value of mastery of the material from the pretest score of 26.92% of students increased to 92.51% of the posttest value. Student responses to documentary films as audiovisual interactive media are considered good. As can be seen from the response indicator value, the average response value is more than 80%. The use of documentary film media for regional tourism potential is generally favored by students.